Makna Takdir dalam Al-Qur’an: Studi Analisis Tafsir Al-Amthal Fī Tafsīr Kitāb Allah Al-Munzal - Saputra, Nanda; Asyari (Sekolah Tinggi Agama Islam Sadra Jakarta), Hasyim (Paradigma: Jurnal Kalam dan Filsafat, 2024)
The issue of the concept of fate and human freedom in Islamic theology involves various perspectives, such as Qadariyah, which emphasizes human freedom, and Jabariyah, which considers fate as absolute decree. Tafsir Al-Amthal combines these diverse views to provide a comprehensive understanding of the verses of the Qur'an. The research focuses on the views of Nāsir Makārim Shīrāzī in his work "Al-Amthal Fī Tafsīr Kitāb Allah Al-Munzal". Thematic method of verses is used to describe and analyze the concept of fate. The research results indicate that fate is Allah's decree which depends on human effort. Makārim Shīrāzī highlights the divine wisdom in fate, where humans have a role in their actions according to the will of Allah.